Status Hukum Penjatuhan Pemutusan Hubungan Kerja dengan Alasan Efisiensi Perusahaan Dampaknya terhadap Eksistensi Perusahaan dari Sudut Pandang Normatif - Maria Sisilia Lou Kelen; Kadek Wiwik Indrayanti (MLJ Merdeka Law Journal, 2022)
This research aims to find out how the legal status of termination of employment (PHK) on the grounds of company efficiency as stipulated in Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation, and also to find out how the impact of violating these rules on the existence or existence or legal status of the company or business entity. This research is a normative legal research which is a procedure for finding truth based on scientific logic from the normative side. The approach used in this research is a statutory approach and comparative approach, which is an approach carried out by comparing laws in one country with other countries or laws from a certain time and laws from another time. The results show that companies or employers who violate the provisions of Article 164 paragraph (3) of the Manpower Law and Constitutional Court Decision Number 19/PUU-IX/2011, both the decision letter of termination of employment (PHK) and the existence or existence of the company are declared null and void and contrary to the 1945 Constitution. Followed by the existence of a norm vacuum regarding the legal consequences if the company is not permanently closed, what is not clearly regulated in the new regulations, namely the Job Creation Law and Government Regulation Number 35 of 2021. The norm vacuum also occurs regarding the process of closing companies that carry out layoffs on the grounds of efficiency. It can be said that neither the old laws and regulations, nor the latest laws and regulations provide legal certainty for the parties.DOI: https://doi.org/10.26905/mlj.v3i1.7927